2016
DOI: 10.1007/s12593-010-0019-2
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Treatment of Dupuytren’s Contracture; Results and Complications of Surgery: Our Experience

Abstract: Dupuytren's disease is one of the fibro-proliferative conditions affecting the palmar and digital fascia. This disease has been known to surgeons and treated by them for at least 200 years. Dupuytren's disease is very common in Northern Europe and also in countries inhabited by immigrants from Northern Europe. Dupuytren's contracture is stated to be uncommon in Indian subcontinent and very little has been written about this disease in India. The authors have however come across 30 patients with Dupuytren's con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 14 publications
(9 reference statements)
0
13
0
Order By: Relevance
“…9 In a study by Khan et al patients were categorized into 3 stages, Stage I is presence of a thickened nodule and band in the palmar aponeurosis and often associated with skin puckering, stage II is stage I plus limitation of extension and stage III is stage II plus flexion contracture. 11 Surgical fasciectomy is a documented effective treatment method, but complications such as digital neurovascular injury and wound-related problems are common. [8][9][10][11][12] Limited fasciectomy (LF) has proven to be curative and effective and most commonly performed of the surgical interventions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 In a study by Khan et al patients were categorized into 3 stages, Stage I is presence of a thickened nodule and band in the palmar aponeurosis and often associated with skin puckering, stage II is stage I plus limitation of extension and stage III is stage II plus flexion contracture. 11 Surgical fasciectomy is a documented effective treatment method, but complications such as digital neurovascular injury and wound-related problems are common. [8][9][10][11][12] Limited fasciectomy (LF) has proven to be curative and effective and most commonly performed of the surgical interventions.…”
Section: Discussionmentioning
confidence: 99%
“…11 Surgical fasciectomy is a documented effective treatment method, but complications such as digital neurovascular injury and wound-related problems are common. [8][9][10][11][12] Limited fasciectomy (LF) has proven to be curative and effective and most commonly performed of the surgical interventions. 12 Denkler et al reported that the limited fasciectomy technique has the lowest recurrence rate out of all surgical and non-surgical methods and is currently the most popular technique used.…”
Section: Discussionmentioning
confidence: 99%
“… 3 Although fasciectomy and selective fasciectomy are similar in terms of functionality and recurrence rates, complication and morbidity rates are strikingly higher with radical fasciectomy. 16 Khan et al 13 employed regional fasciectomy in 27 of their 30 patients and reported excellent and good results in 97% of the patients after five years of follow-up. Özkaya et al 4 retrospectively evaluated patients who underwent partial selective fasciectomy over a 10-year period and observed complications in 16.6% of the patients, but no recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…All patients signed a free and informed consent form. Patients were staged according to system by Khan et al 13 ( Table 1 ) In addition, smoking habits, alcohol use, regular use of medications and accompanying chronic diseases were noted for each patient. Since this study is retrospective in nature, institutional review board approval was not necessary.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation